A Study on the Utilization of Artificial Intelligence (AI) to Enhance the Food and Agriculture Sector (International Journal of Food and Nutritional Sciences, 2022)
"Artificial intelligence" (AI) refers to the study of, and work toward creating computer systems with the "intelligence" necessary to carry out, activities traditionally requiring human intellect. The food sector is embracing artificial intelligence (AI) technology to increase revenues and find novel ways to connect with and service customers in the face of fierce competition and rising consumer demand. Artificial intelligence has been used to improve the efficiency and cost-effectiveness of many processes, including the classification of fresh produce, the management of the supply chain, the monitoring of food safety compliance, the establishment of efficient cleaning in place systems, the prediction of customer preferences, and the creation of brand-new products. The goal of this study is to describe the relevance of artificial intelligence as a predictive interdisciplinary approach integration to enhance the food and agricultural sector; nevertheless, there are certain limits that stakeholders must address. AI might enhance packaging, storage stability, meal combinations, and food standards by creating a more accessible system for managing supply chains. Precision agriculture, robotic farming, as well as drones are the potential of food sectors with AI.